Manganese and ammonia nitrogen recovery from electrolytic manganese residue by electric field enhanced leaching. (1st November 2019) - Tian, Yang; Shu, Jiancheng; Chen, Mengjun; Wang, Jianyi; Wang, Yao; Luo, Zhenggang; Wang, Rui; Yang, Feihua; Xiu, Furong; Sun, Zhi
Abstract: Electrolytic manganese residue (EMR) is a solid waste generated in filters after sulfuric acid leaching of manganese carbonate ore, which contains manganese, ammonia nitrogen and heavy metals that cause damage to environment. In fact, leaching and recovery of manganese and ammonia nitrogen from EMR is the key to the harmless treatment and resource utilization of EMR. In this study, electric field was applied to leach manganese and ammonia nitrogen from EMR. In addition, carbonate precipitation and struvite precipitation methods were used to recover manganese and ammonia nitrogen from leaching solution. The results showed that the leaching efficiencies of manganese and ammonia nitrogen were 88.07% and 91.50%, respectively, when the current density was 35 mA/cm 2, the mass of H2 SO4 and H2 O2 were 9.15 wt% and 3.33 wt%, solid-liquid ratio was 1:5 at temperature of 40 °C leached for 120 min. All heavy metals content in leached EMR except Ni and Cd were below national standard (GB 15618–2018) by electric field enhanced leaching. Meanwhile, manganese and ammonia nitrogen in leaching solution were fractional recovered by MnCO3 and struvite, and the recovery efficiency of manganese and ammonia nitrogen was 98.6% and 98.0%, respectively. This study provides a direction for the effective harmless treatment and resource utilization of EMR. Graphical abstract: Image 1 Highlights: Leaching efficiencies of Mn 2+ and N-NH4 + were 88.07% and 91.50%, respectively. Recovery efficiencies of Mn 2+ and N-NH4 + were 98.60% and 98.00%, respectively. Mn 2+ and N-NH4 + was mainly recycled by MnCO3 and struvite.